Theolinguistic analysis of the monument "Irshadul-muluk uas-salatin" (14th century) in Arabic and Kipchak languages (Journal of Oriental Studies, 2023)
The article provides a theolinguistic analysis of the written monument “Irshadul-Muluk Uas-Salatin” translated from Arabic into Kipchak in the Mamluk period. The connection and continuity of religion and language covering all spheres of human life is a truth that does not require proof. The problem of the formation and development of theolinguistics can be considered independently within the framework of historical theolinguistics on the basis of the linguistic material stored in medieval written monuments from the point of view of national identity. The study and introduction into scientific circulation of medieval religious monuments which are the common property of all Turkic peoples, contributes to the development of the industry, which is an urgent problem not only for linguistics, but also for all humanities. The pragmatic features of the religious language units used in modern Kazakh society are necessary for solving many problems of historical and modern theolinguistics. The use of methods of interpretation, hermeneutic and theological analysis in the study of medieval written monuments makes it possible to obtain valuable information about the language, culture, religion, beliefs, and way of life of the peoples who lived at that time. For this purpose, a linguo-hermeneutic analysis of the linguistic materials stored in the manuscript "Irshadul-muluk uas-salatin" was carried out, within the framework of the religious concept and the peculiarities of the use of the theonym "Tengri" were revealed.